Insertion of Culture through Drama in Arabic Language Learning: A Model for Intercultural Communicative Competence - Budiya, Bahroin; Wargadinata, Wildana; Mubaligh, Ahmad; Lukin, Rose (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study highlights the importance of cultural dimensions in Arabic language teaching through theatre at two Islamic universities in Malang, where language is viewed as a reflection of identity and social values, not merely a communication tool.This study aims to analyze the forms Insertion of Culture. This study employs a qualitative approach with a multi-site case study design using observation, interviews, documentation, drama scripts, and YouTube performance recordings. Data were analyzed through the Miles, Huberman, and Saldana interactive model, while credibility was ensured through triangulation and prolonged field engagement. The findings of the study reveal three main conclusions. In terms of the forms of insertion in Arabic Education Study Program (PBA) at Universitas Islam Negeri Maulana Malik Ibrahim Malang, the findings include: (1) linguistic-cultural aspects, (2) Islamic social values, and (3) visual and performative representations. In the Arabic Language and Literature Study Program (BSA) at the same university, the findings encompass: (1) dramatic script forms, (2) social values, (3) language and dialogue, and (4) character representation. Meanwhile, in Arabic Education (PBA) at Universitas Islam Malang, the results indicate: (1) ideological and local Islamic values, (2) social practices and local traditions, (3) text structure and characterization, and (4) the integration of Arab culture as a linguistic instrument. The contribution of this research is to strengthen culturally-based learning through a drama while enriching theories of communicative competence, performative learning, and Arabic language education from a comparative perspective on the implementation of cultural dimension.